PENGARUH DUKUNGAN SOSIAL DAN BEBAN KERJA MENTAL TERHADAP STRES KERJA PADA PEGAWAI - Bagas Fernando; Willia Novita Eka Rini; Budi Aswin (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2025)
This study aimed to analyze the effect of social support and mental workload on work stress among employees at Muara Bungo II Public Health Center. This study used a quantitative analytic design with a cross-sectional approach. The population consisted of employees at Muara Bungo II Public Health Center, and data were collected using questionnaires measuring social support, mental workload, and work stress. Data analysis was conducted using univariate, bivariate, and ordinal logistic regression analysis. The results showed that social support had a significant effect on work stress among employees. Mental workload also significantly affected work stress levels. Simultaneously, social support and mental workload contributed to employees’ work stress. The study concludes that improving workplace social support and managing mental workload are important to reduce work stress among health workers.